FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERSEPSI SOPIR ANGKOT (ANGKUTAN KOTA) JURUSAN K02 PONDOK GEDE - TERMINAL BEKASI TENTANG KESELAMATAN BERKENDARA DI JALAN RAYA - Nabilah Mayasifa; Ida Wahyuni; Suroto Suroto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
The number of accidents that occurred in the city of Bekasi during January to July 2015 there has been a 134 recorded cases of motor vehicle accidents and cars which is 65% of that occur in urban transportation. City transportation K02 Track Pondok Gede-Terminal Bekasi has the highest accident cases with 32 cases. The high incidence of accidents is because their behavior in the safety aspects of driving on the highway. Theory of planned behavior Ajzen said one factor that determines the direct intention of a person's behavior is perceived behavioral control. Perceived behavioral control is an individual's perception for control to certain behaviors. Therefore, this study aims to determine what factors associated with perception of public transportation drivers about safety driving on the highway on the drivers of public transportation (city transportation) track Pondok Gede Bekasi Terminal using a quantitative research with cross sectional study conducted in December 2015. The population in this study are drivers public transportation K02 with a total samples 82 responden and taken using incidental sampling method. This study using univariate and bivariate using Chi-square test (pvalue <0.05). Based on this research, it is known that from variables (knowledge, motivation and experience) which related to the perception of public transportation drivers about safety driving on the highway is motivation variable (pvalue 0,000). Therefore, it is recommended for drivers of public transport in order to tighten the licensing arrangement in SIM and equipped with the knowledge of laws and regulations related to public transport and highways to improve their perception in safety driving on the highway.